The performance prediction of roadheaders with response surface analysis for underground metal mine - Ozfirat, Kemal M.; Malli, Tahir; Ozfirat, Pinar M.; Kahraman, Bayram (Kuwait Journal of Science, 2017)
Roadheaders are being used in development roads in underground mines. Especially, as total reserve is enough for large investments and mine roads, roadheaders are important to increase production rate. Roadheaders are classified according to the weight head drive or total power. In this study, the effects of several factors on roadheader performance isexamined. The factors examined are power of the machine, weight of the machine, ratio of power to weight, drilling rate index, uniaxial compressive strength and rock mass rating. Instantaneous cutting ratio is used to define the performance of the machine. Response surface methodology and linear regression are used to investigate the relations between these variables. In the results of the study, machine performance is found to be highly correlated with machine power (P), weight (W) and the P/W ratio of the machine.